The Effect of Perception Stimulation Group Activity Therapy on Controlling Ability of Hallucinations in Patients with Schizophrenia - Novi Herawati; Syahrum Syahrum; Tintin Sumarni; Yulastri Yulastri; Abd Gafar; Sri Dewi (Indonesian Journal of Global Health Research, 2020)
Schizophrenia is a personality that is divided between thoughts, feelings, and behavior. One of the most common symptoms of schizophrenia is hallucinations. The highest number of schizophrenic patients with hallucinations was 83 people in the Merpati Room of Prof. HB Sa'anin Hospital in Padang. Therapy is usually given in the management of overcoming hallucinations, one of which is Group Activity Therapy (GAT). The purpose of this study is to determine the effect of Perception Stimulation Group Activity Therapy on the Ability to Control Hallucinations in Schizophrenia Patients at Prof Sa'anin Hospital Padang in 2019. This study uses a Quasi Experiment research design using one group pre-post-test. The population is schizophrenia patients with hallucinations in Prof Sa'anin Hospital in Padang, about 206 persons. Sampling is done by Samples taken were 50 persons, with purposive sampling. The analysis is t-dependent. The results showed a significant difference between the ability of patients between before and after Perception Stimulation Group Activity Therapy with a P-value = 0.000 or α <0.05. It is expected that Prof. Sa'anin Padang's nurses will be more optimal in the implementation of GAT, and improve the implementation of quality GAT according to the grouping of nursing diagnoses so that the ability of schizophrenic patients with hallucinations can be achieved Keywords: schizophrenia, hallucinations, group activity therapy